Do men and women respond differently to blood pressure-lowering treatment? Results of prospectively designed overviews of randomized trials. - Turnbull, F; Woodward, M; Neal, B; Barzi, F; Ninomiya, T; Chalmers, J; Perkovic, V; Li, N; MacMahon, S (2008)
AIMS: Large-scale observational studies show that lower blood pressure is associated with lower cardiovascular risk in both men and women although some studies have suggested that different outcomes between the sexes may reflect different responses to blood pressure-lowering treatment. The aims of these overview analyses were to quantify the effects of blood pressure-lowering treatment in each sex and to determine if there are important differences in the proportional benefits of treatment between men and women. METHODS AND RESULTS: Thirty-one randomized trials that included 103,268 men and 87,349 women contributed to these analyses. For each outcome and each comparison summary estimates of effect and 95% confidence intervals were calculated for men and women using a random-effects model. The consistency of the effects of each treatment regimen across the sexes was examined using chi(2) tests of homogeneity. Achieved blood pressure reductions were comparable for men and women in every comparison made. For the primary outcome of total major cardiovascular events there was no evidence that men and women obtained different levels of protection from blood pressure lowering or that regimens based on angiotensin-converting-enzyme inhibitors, calcium antagonists, angiotensin receptor blockers, or diuretics/beta-blockers were more effective in one sex than the other (all P-homogeneity > 0.08). CONCLUSION: All of the blood pressure-lowering regimens studied here provided broadly similar protection against major cardiovascular events in men and women. Differences in cardiovascular risks between sexes are unlikely to reflect differences in response to blood pressure-lowering treatments.